2012
DOI: 10.1128/aac.05135-11
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Benznidazole by Trypanosomal Type I Nitroreductases Results in Glyoxal Formation

Abstract: Benznidazole, a 2-nitroimidazole, is the front-line treatment used against American trypanosomiasis, a parasitic infection caused by Trypanosoma cruzi. Despite nearly 40 years of use, the trypanocidal activity of this prodrug is not fully understood. It has been proposed that benznidazole activation leads to the formation of reductive metabolites that can cause a series of deleterious effects, including DNA damage and thiol depletion. Here, we show that the key step in benznidazole activation involves an NADH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
187
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 195 publications
(198 citation statements)
references
References 49 publications
6
187
1
4
Order By: Relevance
“…We have now shown that L. major expresses a type I NTR that in the related trypanosomal parasites activates the clinically used prodrugs nifurtimox and benznidazole (26,49,50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have now shown that L. major expresses a type I NTR that in the related trypanosomal parasites activates the clinically used prodrugs nifurtimox and benznidazole (26,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…6B). For both compounds, cells with reduced levels of the nitroreductase were up to 3-fold more resistant to the agent than wild type controls; L. major wild type cells exhibited IC 50 Based on our findings, NBPMs that contain the phosphoramide mustard as part of an acyclic structure and have halogen substituents on the nitrobenzyl ring are the most readily metabolized by the LmNTR enzyme and represent the most potent agents against both L. major promastigotes and amastigotes. Some (LH32, -33, and -34) have IC 50 values of 1 M or less against the intracellular stage without inducing mammalian cell toxicity.…”
Section: Major Expresses a Functional Type I Nitroreductase-a-mentioning
confidence: 99%
See 1 more Smart Citation
“…3B). This mechanism of kinetics, typical for oxidoreductase cascades, has previously been observed when using benznidazole as an electron acceptor under normoxic conditions but not when employing nifurtimox as the substrate (26,27). When reduced by the trypanosomal NTRs, this 5-nitrofuran forms a cytotoxic open chain nitrile while undergoing limited futile cycling.…”
Section: Trypanosomal Type I Nitroreductases Are Fmn Binding Proteinsmentioning
confidence: 98%
“…It is now clear that trypanosomes activate such nitrobased drugs using a mitochondrially targeted, oxygen-insensitive type I NTR, leading to the formation of cytotoxic reduction products (26,27,65). This class of oxidoreductase is largely restricted to bacteria and absent from most eukaryotes, with a subset of protozoan parasites being major exceptions.…”
mentioning
confidence: 99%